WACANA KEKERASAN DAN UPAYA REHARMONISASI KONFLIK DALAM KASUS PERKELAHIAN PELAJAR DI YOGYAKARTA - Ariefa Efianingrum (LPPM UNY, 2006)
This research aims at exploring violence discourse in interaction among students, and efforts to reharmonize the conflict in fight of students in Yogyakarta. Based on the research, students know the violence discourse from electronic media and friendship. The violence discourse they recognize includes violence through language ( words, expression, comments, insult, mocks). They are familiar enough with the rude languages. To some of them, those rude words are the symbol of their close friendship. It is proved that nobody is angry due to the words. That attitude shows that they lack empathy. In addition, violence can fire up violence. Therefore, that violence becomes a portrait of socio-cultural degradation in society.